2011
DOI: 10.1016/j.jmb.2011.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-Binding Domain of Human PARP-1 Interacts with DNA Single-Strand Breaks as a Monomer through Its Second Zinc Finger

Abstract: Poly(ADP-ribose)polymerase-1 (PARP-1) is a highly abundant chromatin-associated enzyme present in all higher eukaryotic cell nuclei, where it plays key roles in the maintenance of genomic integrity, chromatin remodeling and transcriptional control. It binds to DNA single- and double-strand breaks through an N-terminal region containing two zinc fingers, F1 and F2, following which its C-terminal catalytic domain becomes activated via an unknown mechanism, causing formation and addition of polyadenosine-ribose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
149
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 65 publications
11
149
1
Order By: Relevance
“…We also conducted an EMSA assay with a double-hairpin DNA molecule that provides a single 'nick' as a potential binding site for PARP1. In a previous study 21 it was suggested that this DNA bound only a single PARP1 molecule under the conditions used. While we did observe some binding of PARP1-DBD at a protein:DNA ratio of 1:1, in our hands a protein:DNA ratio of 2:1 was required to fully shift the DNA (FIGURE 5c).…”
Section: Dna Damage-dependent Dimerization Of Parp1-dbdmentioning
confidence: 95%
See 3 more Smart Citations
“…We also conducted an EMSA assay with a double-hairpin DNA molecule that provides a single 'nick' as a potential binding site for PARP1. In a previous study 21 it was suggested that this DNA bound only a single PARP1 molecule under the conditions used. While we did observe some binding of PARP1-DBD at a protein:DNA ratio of 1:1, in our hands a protein:DNA ratio of 2:1 was required to fully shift the DNA (FIGURE 5c).…”
Section: Dna Damage-dependent Dimerization Of Parp1-dbdmentioning
confidence: 95%
“…Two recent studies 20,21 , while observing DNA binding modes consistent with dimerization or oligomerization in some circumstances, were able to define buffer conditions and DNA molecules in which 1:1 protein:DNA complexes predominated. These apparently contradictory observations may be rationalized in terms of PARP1 having (at least) two modes of interaction with DNA -a monomeric low activity interaction providing chromatin localization (FIGURE 6a), and a dimeric (or oligomeric) interaction coupled to strand breakrecognition, that brings PARP1 molecules into close proximity and thereby facilitates activation and trans-modification (FIGURE 6b,c).…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%
See 2 more Smart Citations
“…We designed a microarray in which each experimental measurement consisted of a 24-bp double-stranded DNA sequence (Fig. 1B), formed by a hairpin stabilized through a tetraloop (22). This 24-base "window" was scanned through the plasmid in successive measurements; a 4-bp shift per measurement was used to conduct a coarse scan of a large area of pBtoxis, and single base pair shifts were then used for a high-resolution scan of the Bt tubC region ( Fig.…”
Section: Resultsmentioning
confidence: 99%